(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In the article entitled "interdisciplinary connections: literature and music" we tried to show the features of the application of this method of teaching, due to the nature of the taught material and the originality of the writer’s imaginative system, the age groups of students. We have considered several approaches to the application of the method The purpose of the article is to reveal the essence of the above method with the help of interesting observations, paying attention to the principles of studying the material in this way, indicating and justifying the advantages due to the relevant features of this type of training, the features arising from the purpose of training. The novelty of the research is the consideration of various approaches to the application of interdisciplinary communication literature – music and their features. Using the above method, parallel analyses of a work of art and a piece of music were investigated, emphasizing the relationship between words and sound. The relevance of the research is due to the need for modern teaching methods to consider the process of teaching literary works, making it consonant with modern educational programs. In the article we have shown the effectiveness of using various approaches of interdisciplinary communication between literature and music, the possibility of a more meaningful and multilevel study of artistic creativity with their help. As a result of the research, we came to the following conclusions: the use of interdisciplinary literature-music communication contributes to a deeper analysis of the taught material, the formation of students’ skills to create interdisciplinary connections, a large-scale presentation of a work of art, makes the lesson more interesting and meaningful. Key words and phrases - phrases, phonograms, synesthesia, feeling, ideological issues, means of icon painting.